Development of a bioassay method to test activity of cry insecticidal proteins against Diatraea spp. (Lepidoptera: Crambidae) sugarcane stem borers - Ángel-Salazar, Juan Sebastián; Echeverri-Rubiano, Claudia; Rodríguez Chalarca, Jairo; López Gerena, Jershon; Santos, Rafael Ferreira dos; Jurat-Fuentes, Juan Luis; Revynthi, Alexandra M.; Vargas, Germán (2023)
The genus Diatraea (Lepidoptera: Crambidae) includes stem borers representing the most critical sugarcane pests in the Americas. Colombia's most widely distributed and damaging Diatraea species include Diatraea saccharalis, D. indigenella, D. busckella, and D. tabernella. The reduced efficacy of biological tools commonly used in controlling several species highlights the importance of evaluating alternative management strategies, such as transgenic plants expressing insecticidal proteins from the bacterium Bacillus thuringiensis (Bt). The selection of optimal Bt insecticidal proteins for Diatraea control depends on bioassays with purified Bt proteins. Because there is no described artificial diet for borer species other than D. saccharalis and availability of most purified Bt toxins is restricted, this study aimed at developing a bioassay method using fresh corn tissue and providing proof of concept by testing susceptibility to the Cry1Ac insecticidal protein from Bt. Toxicity was evaluated with a single Cry1Ac dose applied directly to corn discs. Stem borer mortality after seven days was higher than 90% for all four tested Diatraea species, while control mortality was below 8%. In addition, we observed that Cry1Ac caused more than 90% weight inhibition in all survivors and delayed development. These results validate the use of this method to determine mortality and growth inhibition due to the consumption of the Cry1Ac protein in each of the Diatraea species. Furthermore, this method could be used to assess other entomopathogenic substances to control these insect pests.